Safety Results for Geographic Atrophy Associated with Age-Related Macular Degeneration Using Subretinal Cord Blood Platelet-Rich Plasma - Stanislao Rizzo, MD; Maria Cristina Savastano, MD, PhD; Benedetto Falsini, MD; Patrizio Bernardinelli, MD; Francesco Boselli, MD; Umberto De Vico, MD; Matteo Mario Carlà, MD; Federico Giannuzzi, MD; Claudia Fossataro, MD; Gloria Gambini, MD; Emanuele Crincoli, MD; Silvia Ferrara, MD; et al. (Ophthalmology Science, 2024)
Purpose: To evaluate the safety of subretinal injection of cord blood platelet-rich plasma (CB-PRP) and its possible effect in eyes affected by geographic atrophy (GA) associated with dry age-related macular degeneration (d-AMD). Design: Interventional, open-label study started in January 2021 with follow-up at 12 months (the Si.Cord Study). This study was a single-center, nonrandomized, sequential-assigned clinical trial conducted in Rome, Italy, at Fondazione Policlinico Universitario Agostino Gemelli IRCCS (ClinicalTrials.gov NCT04636853). Participants: Thirteen patients (26 eyes) with bilateral d-AMD-related GA were enrolled. One eye from each patient (with more advanced GA) underwent CB-PRP treatment, and the fellow eye was considered the control. All patients participated in follow-up at 12 months. Intervention: All 13 eyes received 23-gauge (G) vitrectomy and subretinal injection of CB-PRP using a 41-gauge needle. Main Outcomes and Measures: Best-corrected visual acuity (BCVA) with ETDRS letters, central macular thickness using OCT, and atrophic area measured on en face OCT images were assessed at baseline, 1, 3, 6, and 12 months. Results: The BCVA in the treated group was 34.46 ± 20.8 ETDRS at baseline, 40.84 ± 20.52 at 1 month, 40.07 ± 20.34 at 3 months, 39.38 ± 19.84 at 6 months, and 35.84 ± 18.38 at 12 months. In the untreated group, the BCVA was 53 ± 21.1 ETDRS letters at baseline, 51.54 ± 20.99 at 1 month, 46.62 ± 19.47 at 3 months, 46.85 ± 18.58 at 6 months, and 43.92 ± 17.97 at 12 months (2-way analysis of variance: interaction of treatment by eye or time, P = 0.084). Central macular thickness did not show a significant intereye difference at 12 months (P = 0.97). The atrophic geographic areas tended to increase in both treated and fellow eyes at 12 months (P < 0.0001). No inflammatory reaction, endophthalmitis, retinal detachment, uveitis, or other complications due to the subretinal injection of CB-PRP were observed during the follow-up. Conclusions: Subretinal injection of CB-PRP could be safely used for d-AMD in its GA form. Despite its safety, a larger cohort of patients, and probably a new way of administration, will be needed to understand whether the CB-PRP could have a role in the GA treatment. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.